Evaluation of Waste Management at Atambua New Market, Belu Regency - Ardiyanti Serli Natonis; Mikael Samin; Agustinus Hale Manek (Tinta Emas Institute, 2025)
Waste is something that cannot be separated from everyday life. Waste management includes activities in management such as collection, transportation, disposal of waste and lack of waste handling as found in the research location, namely at the Atambua New Market. This study aims to (1) determine the implementation of waste management in the Atambua New Market, (2) to determine the effectiveness of waste management, and (3) to determine the inhibiting and supporting factors in the implementation of waste management in the Atambua New Market, Belu Regency. The type of research used is qualitative research. Data collection techniques used are interviews and observations. The results of the study indicate that (1) the implementation of waste management in the Atambua New Market, Belu Regency has been running but there are several shortcomings such as the fleet of garbage collectors, cleaning staff, Temporary Disposal Sites (TPS) and tools for cleaning the market (2) waste collection must be paid more attention by cleaning staff to the market corridors, so that management in the market can run well. So it is hoped that there will be additional facilities and infrastructure for cleaning and affirmation from the government for individuals who litter.